Development of Compact Disc Motion and Song Learning to Improve the Physical of Early Children - Yusanti, Arti; Rakimahwati, Rakimahwati (Universitas Negeri Semarang, 2019)
Early childhood is an individual who is developing a process of growth and development that increases when facing development due to an early age. This study aims to develop a compact disk of learning motion and song to improve the physical motor skills of early childhood. The method used is Research and Development (RD) with a 4-D model. This research was conducted at TKIT Adzkia III Kuranji in Padang. In this study, the stages of validation, practicality, and implementation were carried out. The validity test results obtained an average of 86.22% through the practicality test the teacher’s response reached 92.18% and 94.43 for the observation of children’s learning, the effectiveness of the learning activities reached 95.41% and the learning outcomes of the children’s learning 87.35%. Based on these results, the developed compact motion learning and song disc media can be used and practically applied in kindergartens.